Isolation of Chlamydia pneumoniae Clonal Variants by a Focus-Forming Assay - Gieffers, Jens (American Society for Microbiology, 2002)
Chlamydia pneumoniae is an obligate intracellular prokaryotic human pathogen that causes community-acquired respiratory infection and has been associated with atherosclerosis and cardiovascular disease. Unexpected results from genomic sequencing indicate that significant intrastrain polymorphism exists for some C. pneumoniae isolates. These polymorphisms could reflect genotypes with differing disease-causing characteristics. A definitive means to test this hypothesis is to obtain genetically homogeneous clonal populations of the pathogen and test them in models of infection and disease. To date, methods for cloning C. pneumoniae have not been reported. In this study, we describe the isolation of clonal variants with genetic differences in the tyrP locus from a polymorphic respiratory isolate, using a novel focus-forming assay. These results now allow investigations on the biology and pathogenesis of C. pneumoniae clonal genovars that could lead to new insights into the pathogenesis of this important human pathogen.